Prognostic value of FCER1G expression and M2 macrophage infiltration in esophageal squamous cell carcinoma - Wei Peng; Yali Zhao; Ningning Yang; Yan Fang; Yintong Wu; Zhenzhong Feng; Qiang Wu; Xian Wang (Discover Oncology)
Abstract Background FCER1G as an immune-associated protein, which belongs to the immunoglobulin superfamily and is involved in mediating and executing antibody-mediated immune responses. However, the role of FCER1G in cancers remains controversial. Our objectives were to study the association between FCER1G and tumor- infiltrating immune cells (TIICs) as well as the predictive significance of FCER1G. Methods The expression of FCER1G and its prognostic value in ESCC was examined by The Cancer Genome Atlas and Gene Expression Omnibus databases. We also evaluated the relationship between FCER1G expression and 22 TIICs. Immunohistochemistry was used to detect the expression and distribution of FCER1G. Double immunofluorescence was used to detect the co-expression of FCER1G and CD163 positive cells. Kaplan–Meier survival curves and Cox regression analysis was performed to determine the prognostic significance of FCER1G and CD163. Results The analysis revealed that FCER1G was upregulated in ESCC, which was distributed more in the intra-tumor mesenchyme than in the cancer nests. The more infiltration in intra-tumor mesenchyme the worse the overall survival (OS) for patients with ESCC. The infiltration of FCER1G+ cells was positively correlated with that of M2 macrophages and most of the CD163+ M2 macrophages expressed FCER1G. The more the infiltration of FCER1G+ M2 macrophages, the worse the OS of ESCC patients. FCER1G and TNM stage were identified as independent risk factors affecting the OS of ESCC patients. Conclusions FCER1G+ cells infiltration may help to predict the prognosis of ESCC. The combined detection of FCER1G and CD163 has a higher prognostic value.